Opinion of the People of Medan City about the Statement of the Mayor of Medan Regarding Shooting Dead the Begal Offender - Sylvana Patricia (Indonesian Journal of Communication and Social, 2025)
In recent months, the act of robbery in Medan City has become increasingly troubling. Usually the robbery is carried out at night and with quiet street conditions. However, news circulated that the robbery was even carried out in the morning or afternoon where the conditions were crowded (many people were doing activities). The mayor of Medan, Bobby Nasution, did not remain silent seeing the situation. He asked the police to act decisively, including shooting dead the perpetrators if necessary. Therefore, the purpose of this study is to find out the opinion of the people of Medan City about the Mayor's statement regarding shooting dead begalers. The type of research used is qualitative research. Data collection techniques were carried out by interviews distributed through google form to the community in Mabar Village, Medan Deli District, Medan City, totalling 12 research informants. Data analysis was carried out through data reduction, data presentation and conclusion drawing. The results showed that the public's public opinion on the Medan Mayor's call to shoot dead the perpetrators of robbery was mostly approved by the community. The reason is that the community has been very restless and insecure about the actions of the perpetrators of the increasingly troubling Begal, especially for workers who go to or return from work in the middle of the night (early morning), the act of robbery that occurred around UMSU and the Ringroad area which became the main news, as well as the experience of people who have been victims of the action of begalings which is the reason people agree to the call. The existence of the Medan Mayor's call to shoot dead the perpetrators of Begal can provide a deterrent effect for the perpetrators of Begal not to commit acts of robbery again.